Amino acid sequences that determine the nuclear localization of yeast histone 2B. - Moreland, R B (1987)
Histone-beta-galactosidase protein fusions were used to identify the domain of yeast histone 2B, which targets this protein to the nucleus. Amino acids 28 to 33 in H2B were required for nuclear localization of such fusion proteins and thus constitute a nuclear localization sequence. The amino acid sequence in this region (Gly-29 Lys Lys Arg Ser Lys Ala) is similar to the nuclear location signal in simian virus 40 large T antigen (Pro-126 Lys Lys Lys Arg Lys Val) (D. Kalderon, B.L. Roberts, W.D. Richardson, and A.E. Smith, Cell 39:499-509, 1984). A point mutation changing lysine 31 to methionine abolished nuclear localization of an H2B-beta-galactosidase fusion protein containing amino acids 1 to 33 of H2B. However, an H2B-beta-galactosidase fusion protein containing both this point mutation and the H2A interaction domain of H2B was nuclear localized. These results suggest that H2A and H2B may be cotransported to the nucleus as a heterodimer.